Assistance for Pregnant Women Class in Providing Antenatal Care Motivation as an Effort to Improve Maternal and Fetal Health in the Pandemic Covid-19 - Linda Rofiasari; Richa Noprianty; Intan Yusita; Yanyan Mulyani; Agustina Suryanah (Jurnal Peduli Masyarakat, 2020)
The current health program in Indonesia is focused on improving the health status of vulnerable groups, one of which is pregnant women. This is indicated by the high rate of maternal and infant mortality. One of the government's efforts to overcome this problem is the concept of safe motherhood and antenatal care. During the Covid-19 pandemic, most pregnant women did not get medical check-up because they were worried about the corona virus. Therefore, online classes for pregnant women were conducted. This community service method is in the form of interactive education based on information technology online and offline. The targets are all pregnant women who carry out examinations at the Midwife Independent Practice of Yanyan Mulyani, while the targets for pregnancy exercise and prenatal yoga are 35 pregnant women with a gestational age of 28-39 weeks. The implementation technique is divided into three stages, namely the first stage is to assess the level of understanding of the respondent with a pre test, the second stage, namely the implementation of classes for pregnant women by providing online material and the implementation of offline pregnancy and prenatal yoga exercises, and the third stage, namely evaluating the material with post tests . The results of the activity showed an increase in knowledge to be good by 68.6%. Providing information to the class of pregnant women by the facilitator on a regular basis and carried out every week with different materials makes pregnant women make pregnancy visits and regularly attend classes for pregnant women to stay healthy.